Shock Versus Gradualism in Models of Rational Expectations : The Case of Trade Liberalization - Auernheimer, Leonardo; George, Susan (Washington, D.C. : International Monetary Fund, 1997)
This paper provides a new argument for 'shock' versus 'gradualism' in the implementation of trade policies. In the simple context of a small open economy with rational expectations, we consider the comparative welfare effects of eliminating an import tariff either immediately as an unanticipated shock, or gradually over a preannounced length of time. The gradualist policy introduces a distortion in consumption-accumulation decisions and generates welfare costs. And if the gradual change is extended over 'too long' a period, these costs may exceed the long-run benefits of liberalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet